Salário mínimo, Bolsa Família e desempenho relativo recente da economia do Nordeste Minimum wages, poverty alleviation income policies, and the relative performance of the Northeastern economy in Brazil - Alexandre Rands Barros (Brazilian Journal of Political Economy, 2013)
This paper presents the two major hypotheses explaining the relatively higher GDP growth of Northeast, when compared to the one for the whole country. These hypotheses are that governmental transferences towards the poorest and the rises in minimum wages are responsible for such relative performance. They are formally presented theoretically and a method to test their relative role is developed, relying on county data for the period 2000 to 2006. The results indicate that the Bolsa Familia Program had a higher positive impact in the GDP growth rate of the region than the rises in Minimum wage.